2020
DOI: 10.2174/1871530320666200402121917
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels Correlate with Metabolic Syndrome Criteria in Algerian Patients: The Ex-vivo Immunomodulatory Effect of α, 25 Dihydroxyvitamin D3

Abstract: Background: Metabolic syndrome (MetS) is a combination of metabolic disorders with increased risks for several diseases, such as cardiovascular diseases and diabetes. It is associated with the presence of various inflammatory molecules. Vitamin D plays an important role in the regulation of metabolism homeostasis. Objective: The main goal of this work is to investigate vitamin D levels among Algerian MetS patients and its possible outcomes on key molecules of the immune response, as well, the immunemodulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…Due to its roles in diabetes, cancer, autoimmunity, inflammatory responses, as well as muscle and cardiovascular disorders, it has gained increasing interest (6,7). Such as Bouchemal et al have mentioned the important role vitamin D plays in metabolic syndrome (8). Djeraba et al have shown vitamin D deficiency was associated with active Behcet's disease (BD) and after the treatment of vitamin D down-modulates nitric oxide production in BD (9).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its roles in diabetes, cancer, autoimmunity, inflammatory responses, as well as muscle and cardiovascular disorders, it has gained increasing interest (6,7). Such as Bouchemal et al have mentioned the important role vitamin D plays in metabolic syndrome (8). Djeraba et al have shown vitamin D deficiency was associated with active Behcet's disease (BD) and after the treatment of vitamin D down-modulates nitric oxide production in BD (9).…”
Section: Introductionmentioning
confidence: 99%
“… Investigaciones (Bouchemal et al, 2020;de la Guía-Galipienso et al, 2021) indican que el 25-hidroxicolecalciferol puede influir en la función de las células beta pancreáticas, lo que podría mejorar la secreción de insulina. Esto podría ser relevante para el manejo de la diabetes.…”
Section: Resultsunclassified
“…Besides its classic effects, vitamin D presents other lesser-known effects and a wide range of activities. Indeed, recent studies have shown the beneficial role of vitamin D in inflammatory response associated with metabolic syndrome 33 and autoimmune diseases such as Behçet disease 34 . In this context, the immunoregulatory function of vitamin D is argued by downregulation of proinflammatory cytokine and Nitric oxide synthase 2 expression.…”
Section: Vitamin D: Immune-regulatory Effects and Respiratory Infectionsmentioning
confidence: 99%